Orf Virus Detection in the Saliva and Milk of Dairy Goats - Ma, Wentao; Pang, Ming; Lei, Xinyu; Wang, Zishuo; Feng, Hao; Li, Shaofei; Chen, Dekun (Frontiers in Microbiology, 2022)
Orf is a zoonotic and highly contagious disease caused by Orf virus (ORFV) infection. Orf outbreaks in sheep and goats usually lead to high culling rate and mortality in newborn kids and lambs, posing a great threat to the development of goat and sheep industry. Human Orf occurs via direct contact with infected animals or fomites. While this disease is traditionally thought to spread through direct contact, whether other transmission routes exist remains unclear. Herein, we report the detection of ORFV in the saliva and milk of dairy goats without clinical Orf symptoms. Further analyses showed that these ORFV are infectious, as they can induce characteristic cytopathic changes in primary mammary and lip cells. Importantly, these ORFV can induce typical Orf lesions after inoculation in ORFV-free dairy goats. This is the first study showing that live, infectious ORFV can be isolated from the saliva and milk of asymptomatic goats, highlighting novel potential transmission routes of ORFV. These findings provide a novel idea for the prevention and control of Orf spread.